Illustrated report about two exhibitions in Paris in March of 2007 - Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
For more than 10 years, two big agricultural exhibitions have been organised at the same time on the first days of March every year in Paris. Since 1994 the exhibition “SIMAGENA” has been arranged in the exhibition park (Villepinte). The other exhibition (Salon International de l’Agriculture) arranged between 3rd- 11th of March in Paris (Port de Versailles) this year is significant different from the first exhibition by its size and by its topics.On the SIMAGENA exhibition taking place between 4th-8th of March this year, numerous French and foreign agricultural, machine industrial and service firms were introduced on the land of 22 ha, for nearly 200 thousands of visitors. In 2007, in show halls established in two big exhibition halls, 250 pieces of dairy cattle (heifers and cows) and 250 pieces of beef cattle (cows, bulls, heifers, calves) were racing for prizes. On the first 3 days different breeds of beef cattle were racing (on Sunday: Salers, Aubrac; on Monday: Limousin and different breeds of slaughtering animals; on Tuesday: Blonde d’Aquitaine, Charolais), then on Wednesday the Holstein Friesian and on Thursday the Montbéliard breed individuals were called into the show hall. The program was confirmed as an international event by Holstein Friesian breed individuals from 5 countries (Germany, Belgium, The Netherlands, Switzerland and Italy), Limousin breed individuals from 4 countries (Germany, The Netherlands, Switzerland and Italy), and Aubrac breed individuals also from 4 countries (Spain, Ireland, Switzerland, Hungary) arrived at the competition (SIMAGENA, 2007).On the International Agricultural Exhibition (Port de Versailles) among cattle – according to the tradition of earlier years – two breeds (Holstein Friesian and Charolais) rose up in consider of number of animals and level of competition. On this exhibition sheep, goat, pig, horse and also poultry breeders had a chance to show their results. It was a curiosity that dog breeders were represented by 1000 animals and cat breeders also appeared in a required number (Guide de Visite, 2007).In the history of SIMAGENA exhibition for the first time two Aubrac sires housed in Hungary were introduced. The owner of both sires is La Garonnaise Ltd.I recommend my photos taken on the exhibitions to call our readers’ attention.